Application of the behaviour-centred design to understand facilitators and deterrents of hand hygiene among healthcare providers: findings from a formative phase of a cluster randomised trial in the Kampala Metropolitan area - Tonny Ssekamatte; Richard K. Mugambe; John Bosco Isunju; Rhoda K. Wanyenze; Aisha Nalugya; Christine Adyedo; Solomon T. Wafula; Esther Buregyeya; Rebecca Nuwematsiko; Joann Bateman; Julie Balen; Lynnette Lusenaka; et al. (BMC, 2024)
Abstract Background Hand hygiene is known to reduce healthcare-associated infections. However, it remains suboptimal among healthcare providers. In this study, we used the Behaviour-centered Design approach to explore the facilitators and deterrents to hand hygiene among healthcare providers in the Kampala Metropolitan area, Uganda. Methods We conducted a formative qualitative study as part of a cluster randomised trial in 19 healthcare facilities (HCFs). The study used 19 semi-structured and 18 key informant interviews to collect data on hand hygiene status and facilitators and deterrents of hand hygiene. Research assistants transcribed verbatim and used a thematic framework aided by Nvivo 14.0. to undertake analysis. We used thick descriptions and illustrative quotes to enhance the credibility and trustworthiness of our findings. Results About 47.4% of the HCFs had sufficient hand hygiene infrastructure, and 57.9% did not report total compliance with hand hygiene during patient care. The physical facilitator for hand hygiene was the presence of constant reminders such as nudges, while the biological included the frequency of patient contact and the nature of clinical work. The only biological deterrent was the heavy workload in HCFs. The executive brain facilitators included knowledge of workplace health risks, infection prevention and control (IPC) guidelines, and a positive attitude. A negative attitude was the executive brain deterrent to hand hygiene. Recognition, rewards, and fear of infections were the only motivated brain facilitators. Behavioural setting facilitators included proximity to functional hand hygiene infrastructure, the existence of active IPC committees, good leadership, and the availability of a budget for hand hygiene supplies. Behavioural setting deterrents included the non-functionality and non-proximity to hand hygiene infrastructure and inadequate supplies. Conclusions The study revealed low compliance with hand hygiene during the critical moments of patient care and inadequacy of hand hygiene infrastructure. The deterrents to hand hygiene included a heavy workload, negative attitude, inadequate supplies, non-functionality, and long distance to hand washing stations. Facilitators included constant reminders, fear of infections, frequency of patient contact and nature of clinical work, positive attitude, knowledge of IPC guidelines, recognition and reward, good leadership, availability of budgets for hand hygiene supplies, availability and proximity to hand hygiene supplies and infrastructure and active IPC committees. Trial registration ISRCTN Registry with number ISRCTN98148144. The trial was registered on 23/11/2020.